The Hybrid Capriccio Method: A 1D Study for Further Advancement - Ries, Maximilian; Steinmann, Paul; Pfaller, Sebastian (Multiscale and Multiphysics Systems, 2021, 2021)
Polymers and, in particular, polymer composites are known for the enormous adjustability of their mechanical, chemical, and thermal behavior. Multiscale methods are increasingly employed to unravel the polymer microstructure's impact on the material properties. These methods combine the accuracy of particle-based techniques with the efficiency of continuum mechanical approaches. Amorphous polymers pose a special challenge since their microstructure does not continue periodically, and therefore special attention needs to be paid to the particle domain boundary. In this study, we introduce a coupling via an interface between the continuum and the particle domain. Padding atoms as particle representations of the continuum, which serve as interaction partners for the atoms in the particle region, allow for the transfer of displacements and forces between the domains. We present a straightforward 1D example with simple interactions, evaluate the scheme's performance, discuss the resulting energy contributions, and identify an optimal set of coupling parameters. Eventually, this forms the basis for future 3D implementations. <br
Keywords: Particle-continuum coupling; Domain decomposition; Multiscale-modeling